Prominent dyserythropoiesis in four cases of haemophagocytic lymphohistiocytosis. Issue 12 (1st December 2001) - Macheta, M; Will, A M; Houghton, J B; Wynn, R F
Abstract : Haemophagocytic lymphohistiocytosis (HLH) is a disease characterised by peripheral blood pancytopenia secondary to haemophagocytosis of formed blood cells by activated histiocytes. The demonstration of haemophagocytosis may be difficult and the diagnosis may require repeated tissue sampling (including bone marrow, cerebrospinal fluid, lymph nodes, spleen, and liver) and the demonstration of associated clinical or laboratory features. This report describes pronounced dyserythropoiesis in the bone marrow aspirates in four patients with HLH, including familial and secondary cases. In three patients, bone marrow haemophagocytosis was inconspicuous or absent, and the prominent dyserythropoiesis may have suggested an alternative diagnosis. The dyserythropoiesis observed should be added to the constellation of clinical and laboratory features associated with HLH.